Análise retórica: textos motivadores da prova de redação do Enem (2018) - Teixeira de Araújo, Carlos Henrique (2020)
Based on the New Rhetoric by Perelman and Olbrechts-Tyteca (2014), this article aims to analyze the essay test entrance exam of Exame Nacional do Ensino Médio (Enem) of the year 2018 in order to understand the text construction and the arguments used in the “motivating” texts entrance exam through a validated and legitimized pedagogical discourse which is considered supposedly, objective and neutral, and its elicit rhetorical powers triggered in the candidate taking the vestibular university entrance examination, i. e., which discourse direction is taken into consideration and privileged in to the detriment of silencing  others discourses when there is subject of discussion preset by Enem. Furthermore, the analysis is done by applying the discursive and rhetorical theorical content of Perelman and Olbrechts-Tyteca (2014), Amossy (2018), Citelli (1995), and Fiorin (2015).